A critical analysis of research of a mass-housing programme. Issue 6 (18th August 2019) - Kowaltowski, Doris C. C. K.; Muianga, Elisa Atália Daniel; Granja, Ariovaldo Denis; Moreira, Daniel de Carvalho; Bernardini, Sidney Piochi; Castro, Mariana Rios
ABSTRACT: A recent expansion of mass-housing programmes has occurred in emerging economies. The analysis of research on programmes raises questions about what type of research is produced and what its impact is on housing. The Brazilian 'My House, My Life' (Minha Casa, Minha Vida – MCMV) programme demonstrates that more of the same type of housing is produced and that the focus of most research repeats the same mistakes. Three million homes have been built and the research community has examined the programme's social, economic and environmental impacts. A total of 2477 scientific studies on MCMV are analyzed. Few studies were found to assess living conditions from a user perspective at the residential unit scale. Although improvements have occurred on some social issues, the siting of housing on the urban periphery is problematic for urban mobility, social segregation and aesthetic monotony. Also, the design model does not respond to the diverse needs of inhabitants. Opportunities are identified for actions and essential missing research on mass housing. Retrofit strategies are urgent and social cost studies should induce change to the design model. Evidence-based research is needed to support policies and design processes for affordable and quality housing solutions that value users, their needs and aspirations.